2004
DOI: 10.1152/japplphysiol.00073.2004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of blood pressure and morphological traits in cardiovascular-related organs in 13 different inbred mouse strains

Abstract: To better understand the contributions of various genetic backgrounds to complex quantitative phenotypes, we have measured several quantitative traits of cardiovascular interest [i.e., systolic blood pressure, weight (corrected by body weight) of several cardiac compartments and adrenals and kidneys, and histological correlates for kidneys and adrenals] in male and female mice from 13 different inbred strains. We selected strains so that each major genealogical group would be represented and to conform to prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
35
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 28 publications
9
35
1
1
Order By: Relevance
“…Only vasodilation was enhanced in isolated perfused TauTKO hearts during dobutamine stimulation. A possible reason for the inconsistent results between two TauTKO models is the difference of genetic background, since difference of inbred strains affects the cardiovascular phenotypes and susceptibilities against pathological stressors in mice (Barrick et al, 2007;Deschepper et al, 2004). Meanwhile, Warskulat et al also reported that biomarker genes for heart failure, including ANP, BNP and a cardiac ankyrin repeat protein (CARP), are upregulated in TauTKO hearts, which is consistent with our TauTKO model (Warskulat et al, 2006).…”
Section: Taurine Transporter Knockout Micesupporting
confidence: 83%
“…Only vasodilation was enhanced in isolated perfused TauTKO hearts during dobutamine stimulation. A possible reason for the inconsistent results between two TauTKO models is the difference of genetic background, since difference of inbred strains affects the cardiovascular phenotypes and susceptibilities against pathological stressors in mice (Barrick et al, 2007;Deschepper et al, 2004). Meanwhile, Warskulat et al also reported that biomarker genes for heart failure, including ANP, BNP and a cardiac ankyrin repeat protein (CARP), are upregulated in TauTKO hearts, which is consistent with our TauTKO model (Warskulat et al, 2006).…”
Section: Taurine Transporter Knockout Micesupporting
confidence: 83%
“…Figs. [6][7][8]. Based on these findings, the frequency of epithelial hyalinosis affecting extrapulmonary sites was significantly higher in 129S6/SvEvTac females than males.…”
Section: Spectrum Of Nonneoplastic Lesionsmentioning
confidence: 74%
“…Given that NS patients with a PTPN11 mutation present with HCM less frequently than they do with PS and that in previous reports, the Ptpn11 D61G/+ allele in a different mouse background did not exhibit HCM (38), we suggest that the NS mouse model described here represents a distinct strain-specific phenotype. Indeed, it is well appreciated that genetic background can influence physiological and pathophysiological cardiovascular responses (52,53). Thus, there likely exist modifier alleles that influence the penetrance of HCM that in other backgrounds appear to be either repressed and/or activated.…”
Section: Discussionmentioning
confidence: 99%